Exposure to carbon monoxide in underground workings at Zaruma remediation works - Acurio-Rivera, Alexandra Pamela (2024)
The present research work was carried out in Zaruma´s underground workings, a city located in the province of El Oro in the southwest of Ecuador. Zaruma is a city that has been exploited since the 1500's, the urban center sits on a swarm of veins enriched with gold, the antitechnical exploitation has caused the appearance of sinkholes on the surface of the city, with the emergency that occurred in December 2021, partial remediation was carried out corresponding to the filling of the galleries and construction of plugs in order to avoid collapses in the urban area, for the execution of the remediation work required manpower, workers who entered the s underground galleries in which carbon monoxide (CO) was detected, the objective was evaluated the health effects based on the levels of exposure to carbon monoxide. The research methodology is a non-experimental, cross-sectional, descriptive study, with a sample of fifteen workers operating inside the mine, carbon monoxide measurements were taken in the mine workings and symptomatology interviews were applied to the workers taking aspects of age and time of exposure. The results describe that the operators presented symptoms: headaches, nausea, fatigue, weakness; the severity of the symptoms is a function of time and CO concentration. It´s concluded that exposure to CO in high concentrations for a period of time causes intoxication, with headache being the most frequent symptom.